Climatic Change at High Elevation Sites 1997
DOI: 10.1007/978-94-015-8905-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Records from Mongolian and Alpine Ice Cores as Climate Indicators

Abstract: The link between long term changes in the isotopic composition of precipitation and surface air temperature at a given location is of exceptional importance for paleoclimatic studies, as ahs been demonstrated by many recent publications based on the isotope records from polar ice cores. By means of direct comparison with instrumental data, this paper evaluates the potential of the deuterium and oxygen-18 records from two continental glaciers for monitoring climatic trends. The isotopic data presented character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 19 publications
4
44
0
2
Order By: Relevance
“…If robust signals of moisture source changes are present in the stable isotope time series in precipitation, this information could potentially be used to reconstruct a time series of moisture source variability in the Alpine region, e.g. using ice cores from Alpine glaciers (Schotterer et al, 1997;Schwikowski et al, 2005).…”
Section: Implications For Stable Water Isotope Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…If robust signals of moisture source changes are present in the stable isotope time series in precipitation, this information could potentially be used to reconstruct a time series of moisture source variability in the Alpine region, e.g. using ice cores from Alpine glaciers (Schotterer et al, 1997;Schwikowski et al, 2005).…”
Section: Implications For Stable Water Isotope Interpretationmentioning
confidence: 99%
“…Information on moisture sources and transport conditions is often inferred indirectly from the interpretation of stable isotopes in precipitation and paleo archives, such as Alpine glaciers (Schotterer et al, 1997). However, Rozanski et al (1982) concluded that in order to understand the stable isotope signature in local precipitation in Central Europe, the whole transport history, and therefore the influence of circulation patterns must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…7). O in the Alps, in the order of -0.17 / -0.2 ‰ every 100 m (Mariani et al, 2014;Windhorst et al, 2013;Poage and Chamberlain, 2001;Schotterer et al, 1997;Siegenthaler and Oeschger, 1980), the slope of the altitudinal effect is variable (from 0.1 ‰ to 0.6 ‰ / 100 m), depending on the temperature and isotopic fractionation during condensation, altitude, orographic characteristics, moisture source (Horvatinčić et al, 2005), and the trajectories of the air masses (Aouad-Rizk et al, 2005). In the Cordillera Principal geological province, the stable isotope values of streams and rivers showed a slight altitudinal effect in a previous study, attributed to seasonality and changes in the relative contribution from different water sources to streams .…”
Section: Air Masses Retro-trajectory Analysismentioning
confidence: 99%
“…The consequence is a gradient of decreasing natural abundance of heavy isotopes with increasing altitude, observed in many mountain areas of the world (Mariani et al, 2014;Windhorst et al, 2013;Poage and Chamberlain, 2001;Schotterer et al, 1997;Niewodniczanki et al, 1981;Siegenthaler and Oeschger, 1980). Generally, the δ 18 O impoverishment, varies between -0.15 to -0.5 ‰ per 100 m increase in altitude, with a corresponding -1 to -4 ‰ δ 2 H value decrease (Clark and Fritz, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have so far addressed d from ice cores in nonpolar regions (Schotterer et al 1997, Kreutz et al 2003, Ramirez et al 2003, Aizen et al 2005, Vimeux et al 2008. Notably, a decadal resolution d profile obtained from the Dasuopu ice core from the Himalayas (Thompson et al 2000) is the single long term (AD 1000 to 2000) record for this re gion.…”
Section: Introductionmentioning
confidence: 99%